'Past Perfect, Future Progressive': Indexing Society of Canada/Société canadienne d'indexation (ISC/SCI) 2022 conference. (1st December 2022) - Coe, Mary; Kingdom, Ann
Abstract : The Indexing Society of Canada/Société canadienne d'indexation (ISC/SCI) held their 2022 virtual annual conference on 12–14 May. The theme was 'Past Perfect, Future Progressive'. Over 100 participants from around the world listened to seven sessions on topics ranging from the history of indexes to how to teach indexing concepts in the twenty-first century. The practice and business of indexing were covered, with presenters sharing their work methods and tips for staying safe in cyberspace and handling business finances, and there were two themed discussions that enabled indexers to dig into the finer details of their specialities. Many opportunities for networking and socialising with colleagues rounded out another excellent and well-run online conference from ISC/SCI.